Opportunities of collected city data for smart cities. Issue 4 (9th November 2022) - Paiho, Satu; Tuominen, Pekka; Rökman, Jyri; Ylikerälä, Markus; Pajula, Juha; Siikavirta, Hanne
Abstract: This article explores ways to leverage city data in smart cities and how data virtualisation can help overcome some of the barriers and create new opportunities for data usage. By combining data sources, data virtualisation can help overcome technical and regulatory challenges, and create new value. The topic was approached from three perspectives: the exploitation of city data, the potential for data virtualisation to utilise city data, and the detection of gaps for future use of city data. Finnish cities are interested in utilisation of the rich data they have within the city and new data that is gathered by different actors. However, there is a gap between the potential and the current situation. When city data is generated continuously from different functions, the scattered data storages can be utilised efficiently with data virtualisation. The city itself, commercial operators, governments and individuals all benefit about the deeper understanding of city functions. Sharing data from different systems and sectors creates opportunities for measuring also other but financial benefits. In the case of city bicycles studied in the city of Kuopio, expanded usage of the bicycles was seen as benefiting citizens' wellbeing and health. Abstract : The core of our paper is investigating the usability and usefulness of city data to improve smart city services. Furthermore, the research aims at providing clarity for the applicability of data re‐use through data virtualisation in the wider context of data lifecycle and value chain to provide value for both a technical and non‐technical audience.